Repercussions of negatively selective migration for the behavior of non-migrants when preferences are social. (12th April 2019) - Stark, Oded; Budzinski, Wiktor
Abstract: We study how the work effort and output of non-migrants in a village economy are affected when a member of the village population migrates. Given that individuals dislike low relative income, and that migration modifies the social space of the non-migrants, we show why and how the non-migrants adjust their work effort and output in response to the migration-generated change in their social space. When migration is negatively selective such that the least productive individual departs, the output of the non-migrants increases. While as a consequence of this migration statically calculated average productivity rises, we identify a dynamic repercussion that compounds the static one.